A Macro-Ergonomics Perspective on Educational Planning and Design - Zeid, Amir (2015)
The interdisciplinary nature of ergonomics makes it markedly applicable to various fields that involve human performance. Education is one field where ergonomics can make a significant contribution. Yet, educational ergonomics is still not receiving sufficient attention by ergonomists, as opposed to workplace ergonomics [1, 2, 3, 4]. As defined by Smith [5], “Educational ergonomics is that branch of ergonomics/human factors concerned with the interaction of educational performance and educational design”. The extensive literature review provided by Smith [2, 3] in this area has conclusively shown that, with the exception of a few early studies, research in educational ergonomics has tended to focus on “microergonomic issues” [4]. These are issues concerned with the physical environment and its effects on the health of students. However, far too little attention has been paid to the macroergonomic perspective that encompasses learners’ performance, productivity, and wellbeing [2, 6]. Scarcity of research in this area has been attributed to the limited understanding of the interactions between the ‘learner’ and the different components of the educational system [4]. Thus, there is a thirst to move out of the limited microergonomic scope into a higher level holistic perspective [4] that examines user performance in relation to the project/task design. This paper examines the implications of ergonomics in educational setups, emphasizing the importance of employing a holistic ergonomic approach to create and maintain a safe, rewarding, and effective learning environment. Supporting the view that ‘learning’ is a type of ‘work’, in which ‘acquiring skills and knowledge’ corresponds to ‘performance’ [6], this essay aims to investigate the possible parallel relationship between workplace and educational ergonomics. Theories and case studies from both disciplines will be critically examined in an attempt to highlight the role of early ergonomic interventions in reducing user-system conflicts and design errors.